GeSn-on-insulator substrate formed by direct wafer bonding - Lee, Kwang Hong (2016)
GeSn-on-insulator (GeSnOI) on Silicon (Si) substrate was realized using direct wafer bonding technique. This process involves the growth of Ge 1- xSnx layer on a first Si (001) substrate (donor wafer) followed by the deposition of SiO2 on Ge 1- xSnx, the bonding of the donor wafer to a second Si (001) substrate (handle wafer), and removal of the Si donor wafer. The GeSnOI material quality is investigated using high-resolution transmission electron microscopy, high-resolution X-ray diffraction (HRXRD), atomic-force microscopy, Raman spectroscopy, and spectroscopic ellipsometry. The Ge 1- xSnx layer on GeSnOI substrate has a surface roughness of 1.90 nm, which is higher than that of the original Ge 1- xSnx epilayer before transfer (surface roughness is 0528 nm). The compressive strain of the Ge 1- xSnx film in the GeSnOI is as low as 0.10% as confirmed using HRXRD and Raman spectroscopy.